Islamic Workplace Spirituality and Subjective Career Success Among Indonesian Muslim Teachers: The Mediating Role of Career Commitment - Dwiyanti, Retno; Herdian, Herdian; Rahman, Shukran Abd; Meilani, Eka Rizky; Nuryana, Zalik (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2025)
Recently, the role of spirituality in the workplace has gained notable interest. This paper explores how career commitment mediates the impact of Islamic workplace spirituality dimensions (taqarrub, muraqabah, and istiqamah) on subjective career success among Muslim teachers in Indonesia. This study tested hypotheses using partial least squares structural equation modeling (PLS-SEM) on data from 200 respondents (38 male, 162 female) gathered through accidental sampling. The instruments used include the Commitment Career Measure (CCM) to assess career commitment (α = 0.857–0.904), Islamic Workplace Spirituality (IWS) to measure spirituality (α = 0.822–0.836), and the Subjective Career Success Inventory (SCSI) to measure career success (α = 0.891–0.911). All instruments showed good convergent validity (AVE > 0.50) and discriminant validity (Fornell-Larcker and HTMT criteria). The results indicate that career commitment plays a mediating role between Islamic workplace spirituality, particularly istiqamah and taqarub, and subjective career success. Career commitment has a significant positive impact on career success. Both istiqamah and taqarub positively influence career commitment, which in turn enhances career success. However, muraaqabah does not significantly affect career commitment or career success. The indirect influences of istiqamah and taqarub through career commitment are also significant, while muraaqabah's indirect effect is not. The study indicates that Islamic spiritual practices in the workplace can increase commitment and success among Muslim educators. Supporting these practices can help teachers perform better and feel more satisfied with their careers. This is crucial for educational leaders and policymakers to create better school environments.